La política comercial y su impacto en las elasticidades del precio e ingreso del comercio exterior en sectores muebles, calzado y prendas de vestir en Argentina 2003-2015 - Anahi Verónica Rampinini; Nicolás Hernán Zeolla; Lisandro Mondino (Revista Iberoamericana de Estudios de Desarrollo)
The objective of this paper is to evaluate the impact of trade administration policy, particularly Non-Automatic Licenses (LNA, Spanish initials) and the Anticipatory Imports Declaration (DJAI, Spanish initials), on the price and income elasticities of imports into Argentina, based on customs microdata, for the furniture, footwear and clothing sectors between 2003 and 2015. As a result of the intensification of these measures in 2008, and subsequently in 2012, both the LNA and the DJAI reduced the average elasticities for all affected sectors, from ‒1.13 to ‒0.2 in the case of price elasticity and from 4 to 2.5 in the case of income elasticity. Structural change tests and projection of alternative scenarios were run to give robustness to the estimate. This implies that the trade policy measures implemented were effective instruments for moderating import growth in the recovery phase of the economic cycle after the international crisis.